Pengembangan Desa Wisata Berbasis Community Based Tourism (CBT) pada Desa Wisata Air Terjun, Desa Adat Mekar Sari Kabupaten Tabanan - Asianingsih, Ni Luh Nyoman Rai; Dewi, Nyoman Diah utari; Widnyani, Ida Ayu Putu Sri (Penerbit Goodwood, 2023)
Purpose: The existence of a community-based tourism village in Mekar Sari Village, Tabanan Regency-Bali, has not optimally provided economic benefits such as increasing tourist visits to tourism accommodation and the tourism activity support sector at Waterfall Tourism, Mekar Sari Traditional Village, Tabanan Regency. Method: This study uses qualitative research methods and an interpretative descriptive approach that aims to determine an event or situation. Results: As for the results of the research, it was found that the priority of efforts to develop the Leke-leke waterfall tourist attraction and the policy steps in determining the waterfall tourism development effort were based on weaknesses and threats that could hinder the development of the Leke-leke waterfall tourist attraction. The results of the SWOT analysis by testing 4 (four) variables of tourist attraction attraction attraction, accessibility, basic facilities, and supporting facilities found that the tourist attraction attractiveness variable has the greatest implications in attracting tourist visits and developing Leke-leke waterfall tourism in the Mekar traditional village facing threats that come from external factors; however, the Leke-leke waterfall tourist attraction has the strength of internal factors. Contribution: Policies that can be used in developing tourism in the Leke-leke Sari Waterfall, Baturiti-Tabanan District. Limitation: Test the analysis using SWOT (Strengths, weaknesses, opportunities, threats).